Decision making in behavioral strategy - Das, T. K. 1938- (Research in behavioral strategy, 2016)
Decision Making in Behavioral Strategy contains contributions by leading scholars in the field of behavioral strategy research. The 10 chapters in this volume cover a number of significant issues relating to the decision making processes, practices, and perspectives in the field of behavioral strategy, covering diverse topics such as failures in acquisitions, entrepreneurs under ambiguity, metacognition, neural correlates of emotion, knowledge flows, behavioral responses, business modeling, and alliance capability. The chapters include empirical as well as conceptual treatments of the selected topics, and collectively present a wide-ranging review of the noteworthy research perspectives on decision making in behavioral strategy.